ANALISA BIAYA PEMANENAN KAYU MENGGUNAKAN TEKNIK RIL (Reduced Impact Logging) DI IUPHHK-HA PT. WIJAYA SENTOSA, PAPUA BARAT - Muhammad Helmi; Fonny Rianawati; Aurora Putri Modi Sandiana BES (Lambung Mangkurat University-Indonesia, 2020)
The aim of this study is to analyze the cost used of forest harvesting activities which consist of logging, skidding, loading, hauling, and unloading using the Reduced Impact Logging (RIL) technique in the natural forest of PT. Wijaya Sentosa, West Papua. Tools used for this research are stationaries, calculators, and laptop. The data that needs to be collected for cost analysis consists of productivity data as primary data that had taken beforehand, secondary data from the company consist of tree species, tree ages, price of heavy equipment, fuel and lubricant usage data, parts replacement data, and operator wage data. The results obtained from this study are the details of estimated production costs for skidding activities amounting to 101,791 IDR/m3, 5,978 IDR/m3 for loading activities, 3,714 IDR/m3 for unloading activities, and 42,767 IDR/m3 for transportation activities. The total cost of harvesting from logging to transportation is 168,750 IDR/m3.